Impact of polyvinylpyrrolidone and quantity of silver nitrate on silver nanoparticles sizing via solvothermal method for dye-sensitized solar cells - Shamsudin, N.H; Shafie, Suhaidi; Ab Kadir, Mohd Zainal Abidin; Sulaiman, Yusran; Sadrolhosseini, Amir Reza; Abdullah, Abdul Halim (John Wiley & Sons, 2021)
The multiple sizing of silver nanoparticles (AgNPs) were synthesized from the miscible compound of ethylene glycol (EG), polyvinylpyrrolidone (PVP) and silver nitrate (AgNO3) via the solvothermal method. During the synthesis, the PVP-AgNO3 was contemplated as a paramount parameter. Using the simple method of solvothermal, the sizing of AgNPs was easily controlled in accord with the augmentation of PVP-AgNO3 at secured and moderate temperature. In regards to the sizing of AgNPs, the presence of minimum agglomeration, the absorption capability and chemical structures were highlighted through a series of verification includes ultraviolet–visible (UV–Vis) spectroscopy, Fourier-transform infrared (FTIR) spectroscopy and transmission electron microscopy (TEM) analysis. The effectiveness of the synthesized AgNPs was further investigated and compared with the commercial AgNPs by incorporating the AgNPs into titanium dioxide (TiO2) semiconductor film-based dye-sensitized solar cells (DSSCs). Results signified that the spherical AgNPs with produced sizing within the range of 19.6 to 45.2 nm were greatly impacting by tunable quantities of PVP-AgNO3, which was validated in the forms of linear equations. A larger size promotes a slower nucleation rate that conduces agglomeration. In opposition to this, the smallest size of AgNPs develops a faster formation rate of Ag ions into AgNPs, inducing the deterrent of agglomeration in light of notable particle dispersion. The power conversion efficiency (PCE) contributed by the incorporation of synthesized AgNPs into TiO2 is also 41.2% higher than that of the commercial AgNPs-TiO2. This is because the synthesized AgNPs provides less agglomeration which led to a better surface plasmonic effect towards the nanoparticles.